Education and the culture of print in modern America - Nelson, Adam R.; Rudolph, John L., 1964- (Print culture history in modern America., 2010)
"The essays demonstrate the richness and diversity of evidence available for the study of modern print culture in the United States and present an engaging variety of critical perspectives on the history of education."--Thomas Edward Augst, coeditor of Libraries as Agencies of Culture.